2023
DOI: 10.3390/molecules28135282
|View full text |Cite
|
Sign up to set email alerts
|

Anti-α-Glucosidase, SAR Analysis, and Mechanism Investigation of Indolo[1,2-b]isoquinoline Derivatives

Abstract: To find potential α-glucosidase inhibitors, indolo[1,2-b]isoquinoline derivatives (1–20) were screened for their α-glucosidase inhibitory effects. All derivatives presented potential α-glucosidase inhibitory effects with IC50 values of 3.44 ± 0.36~41.24 ± 0.26 μM compared to the positive control acarbose (IC50 value: 640.57 ± 5.13 μM). In particular, compound 11 displayed the strongest anti-α-glucosidase activity, being ~186 times stronger than acarbose. Kinetic studies found that compounds 9, 11, 13, 18, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Figure 3 B shows the Lineweaver–Burk plots of substrate concentration and residual enzyme activity under compound c27 (0~4 μM). It could be observed that all lines with different slopes intersected in the second quadrant, suggesting compound c27 is a mixed-type inhibitor [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 B shows the Lineweaver–Burk plots of substrate concentration and residual enzyme activity under compound c27 (0~4 μM). It could be observed that all lines with different slopes intersected in the second quadrant, suggesting compound c27 is a mixed-type inhibitor [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus, represented as DM, is a chronic endocrine disease characterized by high blood glucose levels (hyperglycemia) and is a significant global health burden. [1,2] The major types of diabetes include type 1 diabetes (T1DM), developed as a result of the destruction of insulin-producing pancreatic β-cells, whereas type 2 diabetes (T2DM), the most prevalent form is characterized by insulin resistance and chronic hyperglycemia. Additionally, there is another type, gestational diabetes, occurring during pregnancy and posing risks to both mother and baby.…”
Section: Introductionmentioning
confidence: 99%